Characterisation of anti-Burkholderia pseudomallei bacteriocin-like compound produced by Burkholderia stagnalis strain K23/3 - Tan, Sherene Hoon Li (2021)
Melioidosis is an infectious disease that is highly endemic in Southeast Asia and Northern Australia. Over the past years, increased reports of melioidosis has emerged from previously unreported areas, especially in tropical developing countries such as Africa, Brazil and Puerto Rico. The causative agent of this disease is Burkholderia pseudomallei, which is intrinsically resistant towards a wide range of antibiotics. Antimicrobial peptides (AMP) are gaining the interests of researchers in treating diseases caused by antibiotic resistant bacteria. An example of AMP is bacteriocin, which is secreted by bacteria that inhibits or kills other bacteria. In this study, we aimed to identify Burkholderia spp. isolated from Sarawak that has the potential in inhibiting the growth of B. pseudomallei and to further characterize the antagonistic compound. A total of 48 environmental isolates of Burkholderia spp. and two isolates of Ralstonia solanacearum were screened against five clinical isolates of B. pseudomallei using spot on lawn assay and flip streak method. Burkholderia stagnalis isolate K23/3 showed clear zones of inhibition (ZOI) in both preliminary tests. Cell-free supernatant (CFS) was obtained from B. stagnalis K23/3 broth culture and was tested via agar well diffusion assay. The antagonistic compound was secreted at the early log phase of the bacterial growth. It was stable in a wide range of temperatures and pH. Treatment with different enzymes revealed that it was sensitive towards Proteinase K, suggesting that it is proteinaceous. The compound of interest was subjected to ammonium sulphate precipitation method to concentrate the protein prior to sodium dodecyl sulphate -polyacrylamide gel electrophoresis (SDS-PAGE). The SDS-PAGE gel was overlaid with indicator B. pseudomallei isolates where the active protein was shown to be less than 7.1 kDa. This is the first report of antagonistic activity demonstrated by B. stagnalis against B. pseudomallei. This finding is important as it may has potential application in the biocontrol of B. pseudomallei in the environment or as potential treatment for melioidosis.